1994
DOI: 10.1051/rnd:19940603
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and availability of essential fatty acids in animal and human tissues

Abstract: Summary ― Essential fatty acids (EFA), which are not synthesized in animal and human tissues, belong to the n-6 and n-3 families of polyunsaturated fatty acids (PUFA), derived from linoleic acid (LA,) and a-linolenic acid (LNA,. Optimal requirements are 3-6% of ingested energy for LA and 0.5-1% for LNA in adults. Requirements in LNA are higher in development. Dietary sources of LA and LNA are principally plants, while arachidonic acid (AA,) is found in products from terrestrian animals, and eicosapentae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
109
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(116 citation statements)
references
References 110 publications
3
109
1
3
Order By: Relevance
“…Changes in hepatic desaturase activity during aging vary according to species (Bourre 2004). They are reported to be decreased in mice (Bourre and Piciotti 1992), but slightly modified (Bourre et al 1990;Dinh et al 1995) or unchanged (Bezard et al 1994) in rats, which is consistent with our results showing age invariance of the conversion coefficients. Despite the unchanging plasma concentrations of esterified n-3 PUFAs with age, each of the respective unesterified concentrations declined (Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Changes in hepatic desaturase activity during aging vary according to species (Bourre 2004). They are reported to be decreased in mice (Bourre and Piciotti 1992), but slightly modified (Bourre et al 1990;Dinh et al 1995) or unchanged (Bezard et al 1994) in rats, which is consistent with our results showing age invariance of the conversion coefficients. Despite the unchanging plasma concentrations of esterified n-3 PUFAs with age, each of the respective unesterified concentrations declined (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…However, reported changes in hepatic desaturase activities during aging vary according to species (Bourre 2004). They are decreased in mice (Bourre and Piciotti 1992), but are slightly modified (Bourre et al 1990;Dinh et al 1995) or unchanged (Bezard et al 1994) in rats. Thus, there is a lack of agreement on liver synthesis of n-3 PUFAs with aging in rodents.…”
mentioning
confidence: 91%
“…Similar effects have been found in rats (Bé zard et al, 1994) and piglets (Theil and Lauridsen, 2007). In contrast, in a human hepatoma cell line a suppression of D6-desaturase mRNA content was seen after the addition of LA or ALA (Portolesi et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to our study, these authors compensated the higher intake of ALA with a decrease in the intake of other fatty acids. We believe that caution should be taken in choosing this exchange approach, as there is evidence that other lipids such as LA, oleic acid and myristic acid (c14:0) can alter hepatic desaturase activity as well (Bé zard et al, 1994;Jan et al, 2004;Portolesi et al, 2008;Rioux et al, 2008). These fatty acids may contribute to the observed opposite effects on plasma DHA in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ló pezFerrer et al (1999) reported that precursors of the n-3 and n-6 families linolenic acid (LNA and LA, respectively) were increased by diets containing FO, whereas AA decreased significantly. Bé zard et al (1994) reported that the fundamental explanation related to the decreased level of AA in serum or tissues is the presence of EPA and DHA in the diet, which are capable of inhibiting n-3 elongation, n-6 FA desaturation and LA metabolism, which is also demonstrated in rats (Grønn et al, 1992). n-3 PUFAs, especially EPA and DHA, are substantial factors in this regard (James et al, 2000;Das, 2006).…”
Section: Growth Performancementioning
confidence: 99%